2021
DOI: 10.1021/acsenergylett.1c00904
|View full text |Cite
|
Sign up to set email alerts
|

Effective Hydrogen Peroxide Production from Electrochemical Water Oxidation

Abstract: The two-electron water oxidation reaction (2e – WOR) is progressively gaining traction as a sustainable approach for in situ electrosynthesis of hydrogen peroxide (H2O2). State-of-the-art 2e – WOR electrocatalysts have shown great promise at low electrical currents yet exhibit diminished electrocatalytic capabilities at larger current densities. Herein, by tailoring the boron doping level of boron-doped diamond (BDD) microfilms, we have fabricated an active, selective, and stable electrocatalyst for the 2e – W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 41 publications
(58 reference statements)
2
52
0
Order By: Relevance
“…A peak %FE of 91.5 % for H 2 O 2 production is additionally attained in 5 m K 2 CO 3 , amongst the highest values reported to date for the 2e − WOR (Figure S4). The observations made in this work regarding the influence of high concentrations of K 2 CO 3 on anodic H 2 O 2 production agree with the experimental findings and theoretical predictions made in previous studies, [19,37−40] where it has been proposed that HO . radicals, generated via the 1e − WOR at the surface of BDD, react with CO 3 2− /HCO 3 − in the aqueous electrolyte to form the transient species CO 3 .− [Eq.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…A peak %FE of 91.5 % for H 2 O 2 production is additionally attained in 5 m K 2 CO 3 , amongst the highest values reported to date for the 2e − WOR (Figure S4). The observations made in this work regarding the influence of high concentrations of K 2 CO 3 on anodic H 2 O 2 production agree with the experimental findings and theoretical predictions made in previous studies, [19,37−40] where it has been proposed that HO . radicals, generated via the 1e − WOR at the surface of BDD, react with CO 3 2− /HCO 3 − in the aqueous electrolyte to form the transient species CO 3 .− [Eq.…”
Section: Resultssupporting
confidence: 92%
“…[10][11][12][13][14][15][16][17] Recently, a transition toward carbonate (CO 3 2À )-based solutions, for H 2 O 2 production, has been noticed, and prominent studies have reported increased H 2 O 2 production rates in Na 2 CO 3 , [18] or K 2 CO 3 /KHCO 3 mixtures. [19] A dedicated study on the influence of carbonate electrolytes and their key properties (concentration, pH, conductivity) on H 2 O 2 electrosynthesis via the 2e À WOR has yet to be carried out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acronyms used in material descriptions are taken from the original works. Data taken from references [15,25,34,[38][39][40][41] Figure 2 highlights that the scope of possible materials is incredibly broad and outside the scope of this discussion. A number of excellent reviews are available for more detailed insights specifically into materials development.…”
Section: Latest Developments For H 2 O 2 Electrosynthesismentioning
confidence: 99%
“…Optimising factors such as doping level and electrolyte composition can address this to give a sizeable increase in faradaic efficiency and production rate. [34] A popular alternative are metal oxides, which give high efficiencies, [35,36] but are usually reported at low current densities (Fig 2C ,D). It is worth noting that it is difficult to compare the activity of many metal oxides to carbon catalysts due to the different surface areas: carbon catalysts tend to be porous whereas metal oxides are often thin films with much lower active areas.…”
Section: Latest Developments For H 2 O 2 Electrosynthesismentioning
confidence: 99%